Balinese Public Perception Towards Climate Change Adaptation (Case Study: Governor's Regulation No. 48 Of 2019 On the Use of Battery-Based Electric Motor Vehicles) - PUTRI, Sukmasari Triana Gita (Journal of Tourism Economics and Policy, 2025)
The Bali Provincial Government has welcomed the Indonesian government's commitment to contribute to reducing greenhouse gas emissions. This study was conducted to determine the perception of the Balinese people towards the climate change adaptation policy that the Bali Provincial Government has made. The study was conducted qualitatively using content analysis. Interviews were conducted with respondents in the Sanur Tourism Area until the saturation point was reached. The results obtained were that most of the climate change perception stimuli were obtained through the sense of taste. There are three groups of perceptions, namely negative, positive, and neutral towards the policy of Governor Regulation No. 48 of 2019. In addition, some people feel the benefits and disadvantages personally and in the community. Based on the results of this study, it can be seen that the tendency of the formation of respondents' perceptions is based on the work environment and daily activities. However, this policy is considered impossible for most people who do not have a choice of transportation modes. It is hoped that this study can provide information to local governments.